ENVIRONMENT ALIVE, DEVELOPMENT SUSTAINABLE I AND POLLUTION I (World Bulletin of Management and Law, 2022)
Thought i basic i from i protection i environment i live i is i that i activity i human i can i bring i as a result of i bad i for i health. i Broken i environment i live i as a result of i action i human i is i threat i for i health i man. i i philosophy this is i different i with i tradition i first i protection i environment i live i i.e. i conservation i and i preservation. i Conservation i meant i as i the i greatest i good i to i greatest i number i for i the i longest i time, i while i preservation i implemented i solely i because i _ nature i need i protected. iThis i thing i due to i because i human i and i environment i is i one i unity i which i no i can i separated, i so that i in i live i and i life i human i environment i and i nature i surrounding i always i synergize. Aproach which i dominant i against i environment i live i as long as i this is i is i setting i which i contains i command i and i supervision. i I idea basically i is i that i individual i especially i they i which i activities i related to i with, i there i whether or not i incentive i market, i will i experience i failure i bear i answer i over i as a result of i activities i against i environment. i By i hence i government i need i for i set i as a result of i environment i in i level i certain i which i can i accepted i and i set i limit i that i no i may i skipped. i Share i part i party, i standard i environment i this is i is i obligation i moral; i but i for i party i else, i will make it i as i cost i internal, and i with i so i fix i failure i market.
Keywords: Environment; Development; Pollution